A Reappraisal of Outcome of Elective Surgery After Successful Non-Operative Management of an Intra-Abdominal Abscess Complicating Ileocolonic Crohn's Disease: A Subgroup Analysis of a Nationwide Prospective Cohort. (22nd October 2020) - Collard, M K; Benoist, S; Maggiori, L; Zerbib, P; Lefevre, J H; Denost, Q; Germain, A; Cotte, E; Beyer-Berjot, L; Corté, H; Desfourneaux, V; Rahili, A; et al.
Abstract: Background and Aims: Few prospective data exist on outcomes of surgery in Crohn's disease [CD] complicated by an intra-abdominal abscess after resolution of this abscess by antibiotics optionally combined with drainage. Methods: From 2013 to 2015, all patients undergoing elective surgery for CD after successful non-operative management of an intra-abdominal abscess [Abscess-CD group] were selected from a nationwide multicentre prospective cohort. Resolution of the abscess had to be computed tomography/magnetic resonance-proven prior to surgery. Abscess-CD group patients were 1:1 matched to uncomplicated CD [Non-Penetrating-CD group] using a propensity score. Postoperative results and long-term outcomes were compared between the two groups. Results: Among 592 patients included in the registry, 63 [11%] fulfilled the inclusion criteria. The abscess measured 37 ± 20 mm and was primarily managed with antibiotics combined with drainage in 14 patients and nutritional support in 45 patients. At surgery, a residual fluid collection was found in 16 patients [25%]. Systemic steroids within 3 months before surgery [ p  = 0.013] and the absence of preoperative enteral support [ p  = 0.001] were identified as the two significant risk factors for the persistence of a fluid collection. After propensity score matching, there was no significant difference between the Abscess-CD and Non-Penetrating-CD groups in the rates of primary anastomosis [84% vs 90% respectively, p  = 0.283], overall [28% vs 15% respectively, p  = 0.077] and severe postoperative morbidity [7% vs 7% respectively, p  = 1.000]. One-year recurrence rates for endoscopic recurrence were 41% in the Abscess-CD and 51% in the Non-Penetrating-CD group [ p  = 0.159]. Conclusions: Surgery after successful non-operative management of intra-abdominal abscess complicating CD provides good early and long-term outcomes.